How Does Antarctic Bottom Water Cross the Southern Ocean?. Issue 7 (9th April 2022) - Solodoch, A.; Stewart, A. L.; Hogg, A. McC.; Morrison, A. K.; Kiss, A. E.; Thompson, A. F.; Purkey, S. G.; Cimoli, L.
Abstract: Antarctic Bottom Water (AABW), which fills the global ocean abyss, is derived from dense water that forms in several distinct Antarctic shelf regions. Previous modeling studies have reached conflicting conclusions regarding export pathways of AABW across the Southern Ocean and the degree to which AABW originating from distinct source regions are blended during their export. This study addresses these questions using passive tracer deployments in a 61‐year global high‐resolution (0.1°) ocean/sea‐ice simulation. Two distinct export "conduits" are identified: Weddell Sea‐ and Prydz Bay‐sourced AABW are blended together and exported mainly to the Atlantic and Indian Oceans, while Ross Sea‐ and Adelie Land‐sourced AABW are exported mainly to the Pacific Ocean. Northward transport of each tracer occurs almost exclusively (>90%) within a single conduit. These findings imply that regional changes in AABW production may impact the three‐dimensional structure of the global overturning circulation. Plain Language Summary: Cooling, ice formation, and mixing near Antarctica create dense ocean waters, known as Antarctic Bottom Water (AABW). Due to their high density, these waters sink and propagate northward to fill the deepest parts of the Southern, Indian, Pacific, and Atlantic Oceans. Hence AABW export has a significant and near‐global impact on deep‐ocean circulation and the distribution of physical properties (e.g., salinity, temperature, dissolved oxygen). However, AABW transport pathways are only partially understood. Here we investigate the transport pathways of AABW from its four principal formation regions, using a state‐of‐the‐art numerical simulation of Earth's oceans. We find that the export occurs via two distinct pathways ("conduits"). The geographical boundaries between these conduits occur near seafloor ridges, and little AABW exchange occurs across them. Circulation pathways within each conduit blend together AABW formed in two of the four main formation regions, and export them to different oceans. Identification of these pathways elucidates the origin of observed trends in AABW properties, and helps to predict where these changes may propagate in the coming decades. Key Points: Antarctic Bottom Water (AABW) export pathways across the Southern Ocean are investigated in a high‐resolution (0.1°) numerical model Weddell‐ and Prydz‐sourced AABW tracers blend together before crossing the Southern Ocean, as do Ross‐ and Adelie‐sourced AABW tracers Weddell/Prydz‐sourced (Ross/Adelie‐sourced) AABW tracers primarily supply the Atlantic and Indian Oceans (Pacific Ocean)